DISPENSASI KAWIN DI BAWAH UMUR (STUDI PENETAPAN PENGADILAN AGAMA PEKANBARU NOMOR 0060/PDT.P/2015/PA.PBR) - Mentari Gemilang; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Underage marriage is a marriage performed by couples in which one or both of them do not meet the minimum age limit for marriage. Underage marriage is permitted with compelling reasons that should be accompanied by the establishment of the dispensation of the marriage of the Religious Court in accordance with the contents of Article 7 Paragraph (2) of Law No. 1 of 1974 About the marriage. The practice of granting dispensation of underage marriage is in need of attention and setting clear, because the provisions in Article 7 Paragraph (2) Marriage Act or the Company Act does not specify a compelling reason for a person to perform underage marriage, provide a loophole for everyone to perform underage marriage. The purpose of this essay, namely: First, to determine the legal basis for the judge to grant the request permits marriage of minors in the Religious Court of Pekanbaru. Second, to determine the factors that are considered by the judge in the Religious Court of Pekanbaru in granted dispensation to marry underage (Study of Religion Pekanbaru Court Decision No. 0060 / PDT.P / 2015 / PA.Pbr). Third, to determine the legal consequences after the child to underage marriage.Keywords: Dispensation Marriage - Marriage Underage - Religious Court